Receptor-Interacting Protein Kinase 3 Inhibition Prevents Cadmium-Mediated Macrophage Polarization and Subsequent Atherosclerosis via Maintaining Mitochondrial Homeostasis - Zhang, Jiexin; Feng, Weijing; Li, Minghui; Chen, Peier; Ning, Xiaodong; Ou, Caiwen; Chen, Minsheng (Frontiers in Cardiovascular Medicine, 2021)
Chronic cadmium (Cd) exposure contributes to the progression of cardiovascular disease (CVD), especially atherosclerosis (AS), but the underlying mechanism is unclear. Since mitochondrial homeostasis is emerging as a core player in the development of CVD, it might serve as a potential mechanism linking Cd exposure and AS. In this study, we aimed to investigate Cd-mediated AS through macrophage polarization and know the mechanisms of Cd-caused mitochondrial homeostasis imbalance. In vitro, flow cytometry shows that Cd exposure promotes M1-type polarization of macrophages, manifested as the increasing expressions of nuclear Factor kappa-light-chain-enhancer of activated B (NF-kB) and NLR family pyrin domain containing 3 (NLRP3). Mitochondrial homeostasis tests revealed that decreasing mitochondrial membrane potential and mitophage, increasing the mitochondrial superoxide (mROS), and mitochondrial fission are involved in the Cd-induced macrophage polarization. The upregulated expressions of receptor-interacting protein kinase 3 (RIPK3) and pseudokinase-mixed lineage kinase domain-like protein (p-MLKL) were observed. Knocking out RIPK3, followed by decreasing the expression of p-MLKL, improves the mitochondrial homeostasis imbalance which effectively reverses macrophage polarization. In vivo, the oil red O staining showed that Cd with higher blood significantly aggravates AS. Besides, M1-type polarization of macrophages and mitochondrial homeostasis imbalance were observed in the aortic roots of the mice through immunofluorescence and western blot. Knocking out RIPK3 restored the changes above. Finally, the administered N-acetyl cysteine (NAC) or mitochondrial division inhibitor-1 (Mdivi-1), which decreased the mROS or mitochondrial fission, inhibited the expressions of RIPK3 and p-MLKL, attenuating AS and macrophage M1-type polarization in the Cd-treated group. Consequently, the Cd exposure activated the RIPK3 pathway and impaired the mitochondrial homeostasis, resulting in pro-inflammatory macrophage polarization and subsequent AS. Knocking out RIPK3 provided a potential therapeutic target for Cd-caused macrophage polarization and subsequent AS.